Swell-shrink behaviour of an expansive soil stabilised by CCR-fly ash (FA) columns and CCR-FA blends. Issue 4 (4th July 2022) - Darikandeh, Farahnaz; Phanikumar, B. R.
ABSTRACT: This paper presents the results of laboratory-scale swell-shrink tests performed in an oedometer on an expansive soil stabilised by calcium carbide residue-fly ash (CCR-FA) columns. The expansive soil used in this study had a swell potential of 11.56%. The CCR-FA columns (3 mm in diameter) were seven in number diametrically arranged in the oedometer. In another series of tests, the expansive soil was directly mixed with the CCR-FA blends. The 3-D volumetric shrinkage of the samples was measured using digital image analysis in five swell-shrink cycles. The results were compared with the shrinkage measured manually. The impact of this treatment on soil morphology was interpreted using SEM. A significant reduction of 62% was observed in swell potential when CCR-FA columns were used at the CCR:FA ratio of 20:80. Uneven swelling patterns for some of the cycles indicate partial loss of cementation. The results of the 3-D volumetric shrinkage indicated only partial success of the treatment in preventing shrinkage. The digital image analysis estimated slightly higher 3-D volumetric shrinkage than that observed through manual measurement. SEM demonstrated the observed changes in soil morphology due to swell-shrink cycles. Further studies would be required to conclude on prevention of shrinkage.